Quality management tools applying in the strategy of logistics services quality improvement - Czajkowska, Agnieszka; Stasiak-Betlejewska, Renata (Serbian Journal of Management, 2015)
Combination of factors such as: properly organized logistics process, lack of nonconformities, transport damages avoiding and transport in accordance Just In Time idea significantly reduces costs and streamlines the entire production process. This paper proposes the quality management tool for the logistics services assessment based on the results obtained in the selected company operating in Eastern Europe. Customers’ expectations and perceptions were compared  using the SERVQUAL method that concerns the service quality assessment in five areas such as: materiality, reliability, promptness, competency and empathy. The research method SERVQUAL allows assessing the service quality level and identifying company areas that requires corrective actions within the improvement process.